Activity of Ocimum sanctum Leaf Extract against Aedes aegypti Larvae: Midgut Histopathological Alteration - Nurhadi Eko Firmansyah; Agus Aulung; Heri Wibowo; Rizal Subahar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2019)
Plant extracts can be used as biolarvacide to kill Aedes aegypti larvae, one of which is Ocimum sanctum leaf extract. The aim of the study was to analyze the effect of O. sanctum leaf methanol extract on Ae. aegypti larvae and histopathological alteration of midgut. The study used an experimental design. O. sanctum leaf extract was made by evaporation methods at 0.1%, 0.25%, 0.5%, 0.75%, and 1% concentration. The experiment was repeated four times for each concentration. Observation of larvae mortality was done after 24 hours of treatment. The results of histopathological observation showed that there was the alteration in epithelial midgut Ae. aegypti larvae. The LC50 value of O. sanctum was 0.66%, while the LC90 value obtained was 1.38%. The results showed that the mortality of Ae. aegypti larvae up to 90% required more than 1% of extract concentration.